A Review on Aluminum Matrix Composites Synthesized by FSP. Issue 1 (23rd February 2023) - Das, Shyam Sundar; Raja, Avinash Ravi; Nautiyal, Hemant; Gautam, Rohit Kumar Singh; Jha, Pushkar; Sharma, Jyoti; Singh, Sudesh
Abstract: Surface modification has been emerged out as a novel value addition process to increase the mechanical as well as tribological execution of the engineering materials in the previous decade. Friction stir processing (FSP) has been one of the best and most recent technologies for improving the surface properties of work material. The current study explores a critical review of the fabrication of aluminum matrix composite by incorporating the abrasive type particles through FSP and analyzing the improved mechanical, thermal, and tribological characteristics of the fabricated composite materials. The study will pave the way for opportunities related to surface modification by FSP.